INTERAÇÃO DE NANOTUBOS DE CARBONO COM CISTEÍNA E BIOTINA: UMA ABORDAGEM TEÓRICA - Aimi, Daniele Morgenstern (2012)
The structural and electronic properties of biotin and cysteine molecules interacting with pure, carboxylated and vacancy-type defects carbon nanotubes was evaluated using ab initio simulations. Carbon nanotubes (NTC) have been used for a variety of applications. Among these, we highlight the use of NTC as sensors for biological molecules. Thus, the objective of this work is to use NTC pure carboxylated and defective molecules interacting with biotin and cysteine in the development of nanosensors for these molecules. Our results showed that the interaction between these molecules and the NTC occurs via a physical adsorption with binding energies ranging from 0.22 to 1.91 eV [0.12 to 1.14 eV] for NTC interacting with biotin [cysteine]. For the carboxylated nanostructure higher binding energies are observed. In this way, carboxylated NTC aren’t interesting for interaction with the molecules, because the eventual removal of these NTC had a high energy cost. The physical adsorption between the NTC and the molecules of biotin and cysteine is of great interest for a possible experimental application of NTC as a biological sensor for these molecules.